Expression of Key Genes Related to Yellow Vein Mosaic Virus Resistance in Okra Via qRT-PCR - , Maninder Kaur, Navraj Kaur Sarao, Mamta Pathak, Abhishek Sharma (Archives of Current Research International, 2024)
Aims: The present study was based on quantitative real time gene expression analysis on the elite cultivar Abelmoschus esculentus Punjab Padmini (susceptible) and wild species Abelmoschus moschatus accession 140986 (resistant) in response to yellow vein mosaic virus disease in okra. Study Design: The staggered sowing of both species was done to coincide the stage of virus inoculation at two true leaf stage. Place and Duration of Study: School of Agricultural Biotechnology and Department of Vegetable Sciences, Punjab Agricultural University, Ludhiana. Methodology: The virus inoculations with viruliferous whiteflies was done, followed by leaf sampling at 0, 1, 3, 5, 10, 15, 20, 25 days post inoculation to know the virus titer at different time points. Results: Though the disease symptoms appeared near leaf margins at 5 days post inoculations yet quantitative real time PCR method was used to measure the relative gene expression of begomovirus coat protein gene. The observations suggest that the virus titer tends to increase at 5 days post inoculations to the higher extent in both species. Interestingly, the maximum fold of begomovirus specific gene expression at 5dpi was observed in resistant species. At five days inoculation time period in the resistant species, the virus replication tends to enhance to resist the viral attack against the strong immune response of resistant species. Conclusion: Our observations confound with the flor-flor hypothesis therefore; we suggest that 5 dpi is recommended for screening of YVMV disease at the gene and genomic levels.